Learning About Our Shameful Past: A Socio-Psychological Analysis of Present-Day Historical Narratives of Italian Colonial Wars - Leone, Giovanna; Mastrovito, Tiziana (International Journal of Conflict and Violence (IJCV), 2010)
A computer-assisted content analysis (Bolasco 2000) of seven textbooks currently used for history teaching in Italian high schools was carried out to ex- amine to what extent past atrocities perpetrated during Italy’s African colonial wars are acknowledged and taught. More specifically, we investigated the relative importance these texts devote to teaching established historical facts or to achieve socio-psychological aims, such as advancing reconciliation processes and protecting the in-group’s social identity. Social psychologists working in the field of intergroup reconciliation usually consider these two aims as partially competing. The models reviewed by Nadler et al. (2008a) all consider the need to protect personal social identity as a source of biases, which the search for historical truth has to accommodate. In contrast, a recent work by Pratto and Glasford (2008) stresses that social identity can play a positive role as a powerful motivation for reconciliation. They suggest that acknowledging historical faults may assist the difficult process of finding a balance between the need for self-esteem and self-integrity and the need to belong. Our results seem to confirm certain aspects of the first group of models, and other aspects of Pratto and Glasford’s review. The crucial point seems to be the use of abstract or concrete terms to describe in-group wrongdoings. Strikingly, more than seventy years after the Italian colonial wars only three textbooks out of seven fully describe atrocities perpetrated by the in-group using clear, concrete terminology; this is consistent with the idea of a tension between reconciliation and justice. On the other hand, the more concrete descriptions, although less frequent, seem better able to protect the in-group’s self-integrity by showing their young readers a clearer acceptance of moral responsibility for the historical faults of their group.